Catheter ablation of electrical storm. (August 2011) - Deneke, Thomas; Lemke, Bernd; Mügge, Andreas; Shin, Dong-In; Grewe, Peter H; Horlitz, Marc; Balta, Osman; Bösche, Leif; Lawo, Thomas
Electrical storm (ES) is defined as the occurrence of ≥ three distinct episodes of ventricular arrhythmia (VA) in patients with implanted defibrillators within 24 h. Whereas conventional strategies for acute rhythm stabilization may be effective in some patients the occurrence of ES impairs survival and predicts recurrent VA. Catheter ablation in the setting of ES is complex and involves decisive strategies for individualized ablation approaches adapted to the patient''s cardiac abnormalities. Success rates have been documented to be between 79 and 94% in larger studies and effective ablation improves survival and freedom from any VA. Ablation should be considered early in the treatment plan and availability may be improved by interhospital collaboration with highly experienced VA intervention centers.